(untitled) (Journal of Engineering, 2023)
Cloud computing (CC) is a fast-growing technology that offers computers, networking, and storage services that can be accessed and used over the internet. Cloud services save users money because they are pay-per-use, and they save time because they are on-demand and elastic, a unique aspect of cloud computing. However, several security issues must be addressed before users store data in the cloud. Because the user will have no direct control over the data that has been outsourced to the cloud, particularly personal and sensitive data (health, finance, military, etc.), and will not know where the data is stored, the user must ensure that the cloud stores and maintains the outsourced data appropriately. The study’s primary goals are to make the cloud and data security challenges more understandable, to briefly explain the techniques used to achieve privacy and data integrity, to compare various recent studies in both pre-quantum and post-quantum, and to focus on current gaps in solving privacy and data integrity issues.